Cultivating knowledge: the adoption experience of learning management systems in agricultural higher education - Sobhani, Seyed Mohammad Javad; Jamshidi, Omid; Fozouni Ardekani, Zahra (Frontiers in Education, 2025)
IntroductionThe emergence of COVID-19 and its associated challenges necessitated a rapid shift in Agricultural Higher Education (AHE) toward innovative non-attendance training methods, particularly Learning Management Systems (LMSs).MethodsTo investigate this paradigm shift, an integrated framework combining the Technology-Organization-Environment (TOE) framework and the Technology Acceptance Model (TAM) was employed to provide a comprehensive model for understanding LMS adoption. This study analyzed survey data collected from agricultural students in Iran (N = 385) using structural equation modeling (SEM).ResultsThe findings indicate that the technological context of LMSs significantly influences both perceived usefulness and perceived ease of use, while the environmental context only affects perceived usefulness. In contrast, organizational factors were found to have no significant impact on these components. Furthermore, the analysis revealed a positive relationship between perceived ease of use and perceived usefulness, which subsequently fosters a favorable attitude toward LMSs and strengthens behavioral intention to adopt them.DiscussionThis study underscores the critical need for enhancing information technology infrastructure in agricultural education, advocating for a synergistic approach between government and universities to integrate e-learning with traditional educational methods. The proposed integrated model not only demonstrates strong explanatory power but also facilitates student engagement with LMSs, paving the way for innovation and knowledge exchange in the agricultural sector. These insights highlight the potential for LMSs to transform agricultural education, particularly in the context of global disruptions such as the COVID-19 pandemic.